2018
DOI: 10.1159/000488342
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Biomarkers for Cholangiocarcinoma

Abstract: Background: Cholangiocarcinoma (CCA) represents the second most common primary liver malignancy. The incidence rate has constantly increased over the last decades and CCA patients face a dismal prognosis with a 5-year survival rate of less than 5% for advanced stage of disease. Surgical tumor resection has remained the only potentially curative treatment option in daily practice but is often not feasible due to advanced disease stage at initial diagnosis. Summary: The early detection of cholangiocarcinoma is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 68 publications
0
11
0
2
Order By: Relevance
“…7 Nevertheless, the clinically available tumor markers CEA and CA19-9 are mostly used to monitor tumor response to chemotherapy, and the existing preoperative stratification tools often fail to identify the ideal candidates for a surgical treatment approach. 33,34 Herein, we showed that serum levels of suPAR are elevated in 2 independent cohorts of patients with BTC who underwent surgical tumor resection compared to patients with PSC and healthy controls. Moreover, our data provided evidence that suPAR serum levels before and after surgery might yield valuable information on the patients' postoperative outcome.…”
Section: Discussionmentioning
confidence: 90%
“…7 Nevertheless, the clinically available tumor markers CEA and CA19-9 are mostly used to monitor tumor response to chemotherapy, and the existing preoperative stratification tools often fail to identify the ideal candidates for a surgical treatment approach. 33,34 Herein, we showed that serum levels of suPAR are elevated in 2 independent cohorts of patients with BTC who underwent surgical tumor resection compared to patients with PSC and healthy controls. Moreover, our data provided evidence that suPAR serum levels before and after surgery might yield valuable information on the patients' postoperative outcome.…”
Section: Discussionmentioning
confidence: 90%
“…Cholangiocarcinoma (CCA) is the second most common primary liver tumor after HCC 89 . CCA and HCC display heterogeneity at both morphologic and molecular levels 90 .…”
Section: Hh Signaling In Liver Cancersmentioning
confidence: 99%
“…Cholangiocarcinoma (CCA), also known as bile duct cancer, is the second most common malignancy of the liver, accounting for 10%‐20% of primary hepatic malignancies . CCA is classified as intrahepatic, perihilar, or distal based on anatomic location .…”
mentioning
confidence: 99%